Temporal Trends in Colorectal Cancer Incidence and Case Numbers among Individuals Aged 45-49 in the US During 2001-2019 - Li, Chunmei; Chen, Tianle; Chen, Huimin; Zhang, Bo; Sun, Bing; Zhou, Pengyang; Li, Qiken; Chen, Weiping (Cancer control, 2025)
Objective: This study aimed to update the temporal trends for the incidences and case numbers of colorectal cancer (CRC) among individuals aged 45-49 in the US from 2001 to 2019. Methods: Patients were obtained from the National Program of Cancer Registries and Surveillance, Epidemiology and End Results Program (NPCR-SEER) database. Their age-adjusted incidence rates (AAIR) were calculated using the SEER*Stat software. Results: As high as 48.4% (125 604 cases) of the 259 700 early-onset CRC were diagnosed in individuals aged 45-49. Of these, 54.2% were males, and 40.7% were located in the rectum. Adenocarcinoma accounted for 93.9%, 96.5%, and 84.6% of proximal, distal colon, and rectal cancers, respectively. The incidences of proximal colon adenocarcinoma showed a significant increase, with an average annual percentage change (APC) of 0.7 from 2010 to 2019, while the case numbers remained stable from 2001 to 2019. In contrast, distal colon adenocarcinoma displayed increased incidences at an APC of 1.3 and an average increase of 17 cases annually over the study period. Rectal adenocarcinoma showed more rapid increases in incidence, with an average APC of 1.6 and an average increase of 27 cases per year. These rising incidences were predominately observed in non-Hispanic whites (NHWs). Conversely, non-Hispanic black (NHB) females showed decreased incidences of proximal and distal colon adenocarcinoma. Additionally, the incidences and case numbers for carcinoids significantly increased in the rectum but not in the colon. Conclusions: This study reveals distinct patterns of temporal trends in CRC incidences and case numbers among individuals aged 45-49. Further research is necessary to understand the underlying causes of the differences and to develop more effective preventive strategies to reduce the incidence of early-onset CRC.